A study of the development commitment of editors of public secondary school papers - Ver, Mary Lou Agbayani 1929-
The bases of this study are a survey conducted among forty high school editors of official school papers of public secondary schools in the three geographical regions of the country and a content analysis of fifty published editorials of twenty-five respondent editors. The development commitment of each editor is defined as a composite of his reactions to six development values identified by the International Studies of Values in Politics. The researcher made use of the development values scale in order to find out the intensity of commitment of the respondent editors toward six development values.
Originally presented as the author's thesis; University of the Philippines, 1975.
Keywords: College and school journalism; Editors